ANALISIS MENGENAI ZAKAT PROFESI KAITANNYA DENGAN PAJAK PENGHASILAN - Rochaeti, Etty (Jurnal Wawasan Yuridika, 2011)
Tithe, as one of the Islamicpillars of faith is the obligationfor every Moslem who can afford to pay for it, and it is intended for those who are entitled to receive it. With good control and management, tithe is a very significant source of fund which can be used to improve and develop social welfare for all walks of life. Tithe is worship in the area of property containing great and glorious wisdom and benefits, both related to muzakhi (a person who gives tithe), mustahiq (a person who receives tithe), treasures, and also societies. The regulation of tithe distribution has been regulated in Act No. 38 of 1999 on Tithe Management with Decree of Minister of Religion No. 581 of 1999 on Implementation of Act on Tithe Management. Pertaining to the relationship between tithe and tax, primarily income tax according to Act No. 36 of 2008 on Income Tax, it can be explained that; to determine the size of the taxable income of the taxpayer in the country and fixed business formshould not be deducted, unless income tithe which is paid by tax payer, individual, Moslem, or tax payer of a domestic corporate body owned by Moslem given toAmil Board of Tithe and Amil Agency of Tithe, established and endorsed by the government.Keywords: Profession Tithe - Income Tax